Study on anatomy and postnatal development of sublingual salivary glands in Black Bengal goat (Asian Journal of Medical and Biological Research, 2020)
There are three pairs of salivary glands in Black Bengal goat namely parotid, mandibular and sublingual salivary gland. Information regarding the sublingual salivary gland is very limited and confined in adult goat only, no reports available concerning the postnatal development of the goat sublingual gland to date. Present study is carried out to fill up the gap of information regarding this gland. In day old kid the sublingual gland is measured 2.5 ± 0.30 cm in length, 0.25 ± 0.08 cm in breadth, 0.15 ± 0.01 cm in thickness and 0.09 ±0.01 g in weight which became little more than double in each parameter in adult. The main sublingual duct is formed by the union of 5-7 radicles from monostomatic part of the gland and opened at sublingual caruncle. 26-30 small tortuous ducts arise from the polystomatic part and opened independently in a row of microscopic orifices of the sublingual fold. Gradual histological development shows the glandular units composed of tubule-alveolar acini which are mostly mucous in type. The mucous acini composed of pyramidal shape cells resting on a basement membrane. In day old kid, the acini have distinct lumen. The cells contain rounded nuclei at their basal part and lack of zymogenic granules indicating less functional state of the glands. Along the advancement of age the size of lobes and lobules are increased, the lumens of the mucous acini reduced in size, nuclei of the cells became flattened the zymogenic granules increased gradually. Mixed acini are more than the serous acini where a serous demilune is attached on a mucous acinus. The serous acini were less in number.Asian J. Med. Biol. Res. June 2020, 6(2): 328-333